Lost in translation? Translation as a valid tool for the EFL classroom - Antón Remírez, Susana; Lázaro Ibarrola, Amparo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2011)
The use of translation in foreign language classrooms seems to have fallen into oblivion. In fact, a wealth of works has advised against its use. However, some recent works also indicate that the L1 might be a very useful tool when learning a new language. The present study aims to contribute to this debate by testing the effectiveness of a reverse translation activity (Spanish into English) in the acquisition of English by 15 Spanish students in the 4th year of Compulsory Secondary Education in high school. The study focuses on several grammatical structures as well as on a set of vocabulary items through a treatment-post-test design. The learners were also asked to fill in a questionnaire with their impressions about the activity. The results showed that translation was very helpful for both the acquisition of vocabulary and the grammatical structures with the only exception of the structure “be used to”. The answers from the students’ questionnaires also showed that the activity was motivating for them. In light of these results, the value of translation in high school is discussed and possible lines for future research are indicated.